PENGARUH PEMAHAMAN PERPAJAKAN, KESADARAN PERPAJAKAN DAN PENERAPAN EFILING TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA BATAM - Silalahi, Monalisa; Ompusunggu, Hermaya (SCIENTIA JOURNAL, 2024)
The study aims to evaluate the effect of understanding taxation, tax awareness and the application of e-filing on taxpayer compliance in Batam City. The methodology used is quantitative; numerical information from the data provided will be statistical tests related to taxpayer compliance. The population is 400,034 individual taxpayers recorded in KPP Pratama Batam Selatan in 2022. The sample collection method used is a random sampling technique through a random selection process. The results of the sample calculation of researchers applying the Slovin formula with a population of 400,034 and an error rate of 10%. Researchers get 99.9 respondents, rounded up to 100. The data collection technique uses a questionnaire in which respondents provide answers to a series of questions posed using a G-forrm measured on a Likert scale. Tests carried out in this study include descriptive analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test t test, f test and coefficient of determination test. SPSS 26 program used to manage data. The partial findings are that tax understanding, awareness, E-Filing Implementation has a positive effect on taxpayer compliance, simultaneously that Taxpayer Compliance (Y) is significantly influenced by the variables of Tax Understanding (X1), Tax Awareness (X2), and E-Filing Implementation (X3).